Magnetic resonance imaging in clinically isolated lesions of the brain stem. - Ormerod, I E (1986)
Twenty-seven patients with an isolated brain stem syndrome, thought to be due to demyelination, were examined by magnetic resonance imaging (MRI). A brain stem lesion was identified in 25, and clinically silent lesions outside the brain stem were demonstrated in 20. MRI was more sensitive than evoked potentials in detecting brain stem and other lesions. The scan findings were compared with those in 23 patients with multiple sclerosis, who had chronic brain stem dysfunction, with particular reference to the distribution of abnormalities and the MRI characteristics of the lesions. The relaxation times, T1 and T2, of the lesions were measured by MRI. These values were seen to fall in serial studies of acute lesions, but remained unchanged in the chronic lesions. MRI may therefore allow the age of lesions to be assessed.